(untitled) (ENTHYMEMA, 2024)
The article provides a close reading of the novel Το βιβλίο της Κατερίνας [The Book of Katerina] by Auguste Corteau, highlighting its connections and divergences from Το τρίτο Στεφάνι [The Third Wedding Wreath] by Kostas Taktsis. It explores issues of social gender, family, and autobiography through the lens of camp discourse. From a theoretical perspective, the analysis builds on Fabio Cleto’s considerations of queer readings of camp discourse.